GENETIC VARIABILITY AND CHARACTER ASSOCIATION STUDIES IN CHICKPEA (Cicer arietinum L.) WITH SPECIAL REFERENCE TO TRAITS AMENABLE TO COMBINE HARVESTING - V. JAYALAKSHMI*, A. TRIVIKRAMA REDDY, B. VISHNU and M. MOHAMMED IMRAN, (The Journal of Research ANGRAU, 2020)
The study was taken up with 100 advance chickpea breeding lines obtained from different institutesduring Rabi, 2016-17 to assess the genetic variability and character association for traits contributing tocombine harvesting. Two advance breeding lines-NBeG 864 (3.1 t ha-1) and NBeG 862 (2.7 t ha-1) whichhad the first pod bearing node 30 cm from above the ground; plant height greater than 50 cm and angle60°or above between the main axis and primary branch with significant yield advantage over machineharvestable check cultivar ‘HC 5’ were identified. Genetic variability as measured in terms of phenotypiccoefficient of variation (PCV) and genotypic coefficient of variation (GCV) was moderate for height of thefirst pod and low for angle of the primary branch and plant height. Yield attributing traits viz., number ofprimary branches, number of secondary branches, 100 seed weight, shoot biomass and days to 50 percent flowering exhibited moderate PCV and GCV values. Height of the first pod, days to 50 per centflowering and 100 seed weight exhibited high heritability and high genetic advance indicating the scope forgenetic improvement of the traits through phenotypic selection. Character association studies revealedshoot biomass as a major contributing character for seed yield in chickpea. Plant height and height of thefirst pod exhibited a strong positive association between themselves and with shoot biomass. Also, interse correlations among the positively associated traits with seed yield viz.,100 seed weight, number ofsecondary branches and plant height with shoot biomass showed significance in breeding genotype ssuitable for combine harvesting.